The Influence of Products, Promotions And Discounts On Car Purchase Decisions at PT. Kumala Brilliant Immortal Wuling Motors Parepare City - Pandi Putra; Ulyana Muslimin (Universitas 17 Agustus 1945 Surabaya, 2023)
The Influence of Products, Promotions and Discounts on Car Purchase Decisions at PT. Kumala Brilliant Immortal Wuling Motors Parepare City This study aims to determine how much influence the quality of the product, promotions and discounts on the decision to buy a car at PT. Kumala Brilliant Immortal Wuling Motors Parepare City. The method of analysis used in this research is the method of observation, interviews, questionnaires, and documentation as well as the method of determining the sample using the Roscoe approach and obtaining 40 respondents. The analytical method used is Multiple Linear Analysis. The results of this study indicate the influence of products, promotions and price discounts simultaneously on car buying decisions at PT. Kumala Brilliant Immortal Wuling Motors Parepare City. This is evidenced by the statistical results of Fcount of 99.778 with a significance of 0.000. Because the significance value is less than 0.05 (0.000 < 0.05), this study succeeded in proving